Analysis of digitalized ECG signals based on artificial intelligence and spectral analysis methods specialized in ARVC. (3rd September 2022) - Papageorgiou, Vasileios E.; Zegkos, Thomas; Efthimiadis, Georgios; Tsaklidis, George
Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited heart muscle disease that appears between the second and forth decade of a patient's life, being responsible for 20% of sudden cardiac deaths before the age of 35. The effective and punctual diagnosis of this disease based on electrocardiograms (ECGs) could have a vital role in reducing premature cardiovascular mortality. In our analysis, we first outline the digitalization process of paper‐based ECG signals enhanced by a spatial filter aiming to eliminate dark regions in the dataset's images that do not correspond to ECG waveform, producing undesirable noise. Next, we propose the utilization of a low‐complexity convolutional neural network for the detection of an arrhythmogenic heart disease, that has not been studied through the usage of deep learning methodology to date, achieving high classification accuracy, namely 99.98% training and 98.6% testing accuracy, on a disease the major identification criterion of which are infinitesimal millivolt variations in the ECG's morphology, in contrast with other arrhythmogenic abnormalities. Finally, by performing spectral analysis we investigate significant differentiations in the field of frequencies between normal ECGs and ECGs corresponding to patients suffering from ARVC. In 16 out of the 18 frequencies where we encounter statistically significant differentiations, the normal ECGs are characterized by greater normalized amplitudes compared to the abnormal ones. The overall research carried out in this article highlights the importance of integrating mathematical methods into the examination and effective diagnosis of various diseases, aiming to a substantial contribution to their successful treatment. Abstract : A complete digitalization methodology concerning paper‐based ECGs accompanied by a spatial filter aiming to eliminate undesirable dark regions not corresponding to ECG waveforms is presented. The utilization of a low‐complexity convolutional neural network for the detection of arrhythmogenic right ventricular cardiomyopathy (ARVC), accomplishes high classification accuracy on disease whose major identification criteria are infinitesimal millivolt variations in the ECG's morphology. Finally, significant differentiations between normal and ARVC ECGs in the frequency field are investigated, while the overall research carried out in this article highlights the importance of integrating mathematical methods into the effective diagnosis of various diseases, aiming to a substantial contribution to their successful treatment.